FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN (FATIGUE) PADA PERAWAT - Putri, Andi Nadya Eka; Utami, Utami; Putra, Ryryn Suryaman Prana; Arniawan, Arniawan (Ensiklopedia of Journal, 2025)
Abstract: Nurses are one of the key components in hospital health services. Work fatigue that is not adequately addressed can cause various serious problems in the work environment, including an increased risk of workplace accidents. The purpose of this study is to determine the factors associated with fatigue in nurses. The research design used in this study is cross-sectional. The study was conducted at Sundari General Hospital. The study was conducted in February 2025. The study population consisted of all nurses at Sundari General Hospital. The sample consisted of 65 people. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between length of service (p value: 0.047) and workload (p value: 0.00) with work fatigue among nurses. It is recommended that hospital management recruit additional nurses to compensate for the number of patient visits. Providing occupational safety and health (OSH) education on work fatigue management for nurses and ensuring adequate nutritional intake are also necessary as preventive measures against more serious work-related illnesses.Keywords: Workload, Work Fatigue, Nurses.